The Moderating Effect of Empowerment in the Relationship Internet Use in Health and Shared Decision-making between Patient and Doctor - Zoghlami, Meryem; Ayeb, Salma; Ben Rached, Kaouther Saied (International Review of Management and Marketing, 2019)
This paper examines the relationship between patient online health use, empowerment and treatment decision-making. A quantitative survey of 114 patients with chronic diseases highlights the impact of Internet use on shared decision-making. The study also examines the moderating effect of patient empowerment. The results indicate that the relationship between online health use and shared decision-making is stronger under a high level of empowerment. Keywords: online health use, doctor-patient relationship, shared decision-making, empowerment. JEL Classifications: I12, M31 DOI: https://doi.org/10.32479/irmm.9012